The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.hpb.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant chemoradiation on survival in patients with resectable cholangiocarcinoma

Abstract: Background: The ideal adjuvant therapy for resected cholangiocarcinoma remains controversial. Na-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Several studies related lymph-node status (regional lymph nodes metastases) to poor survival. [6,7,13,18] The same result was seen in this study ( P = .032). Our study also found a relationship between liver reduction rate >30% and treatment outcome ( P = .016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies related lymph-node status (regional lymph nodes metastases) to poor survival. [6,7,13,18] The same result was seen in this study ( P = .032). Our study also found a relationship between liver reduction rate >30% and treatment outcome ( P = .016).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, MST was 40 months, 2-year OS was 72.4%, and LC was 65.3%. The 40-month MST was similar to, or longer than, that in previous studies (13–37 months) [6,7,12,13,1821] ; OS was also similar to previous studies. [6,2224] A few reports clearly address in-field recurrence.…”
Section: Discussionsupporting
confidence: 88%
“…However, in three of the studies, the margin status was R0 or R1, and R0 accounted for the majority of patients. The 2year OS and MST rates of patients who receive adjuvant chemoradiotherapy or radiation therapy range from 57.9-60% and 30.2-36.9 months, respectively [4,26,27,28,29]. In these reports, only R0 or R1 patients were included, and the median radiation doses ranged from 45-59.4 Gy, and 28-100% of patients received concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensitivity of these tests in the diagnosis of CCA is limited, especially in the early stages of the disease [ 25 ]. Management strategies include multispecialty treatments, with consideration of surgical resection, targeted radiation therapy, and systemic chemotherapy [ 24 , 26 , 27 ]. Surgical resection is the only potentially curative treatment, but the majority of patients present with advanced cancer and recurrence after resection is common [ 16 ].…”
Section: Epidemiology Risk Factors Diagnosis and Treatment Of Ccamentioning
confidence: 99%